Changes in muscle coordination during butterfly swimming at submaximal and maximal efforts - Yamakawa, K. K.; Sengoku, Y.; Takagi, H. (Sports Biomechanics, 2026)
The aim of this study was to clarify the changes in muscle coordination during butterfly swimming at different swimming speeds. Eight female swimmers performed 25 m butterfly at 60%, 80% and 100% effort. Two-dimensional motion analysis was conducted using video data. Surface electromyography was recorded from 12 muscles in the right upper limb, lower limb, and trunk, and muscle synergies were identified using non-negative matrix factorisation. The kinematic analysis showed that the catch phase of the arm stroke shortened with increasing speeds. For most swimmers, four muscle synergies were extracted across different speeds. The spatial components of the four synergies involved in the pull, push, recovery movements of the arm stroke and downward kick were similar across different speeds. In contrast, the drive timing of the three synergies changed earlier at the highest level of effort. In addition, the amount of earlier timing in Synergy 1 between 60% and 100% effort levels was positively correlated with the earlier start of the pull phase (r = 0.72, p < 0.05). Overall, these findings indicate that speed-related kinematic changes are linked mainly to shifts in synergy timing rather than changes in individual muscle activity.